Augmented and mixed reality in mandibular reconstructive surgery: a systematic review - Tyler Ferdinands; Anirudh Krishnan; Onur Bas; Allison Sutherland; Michael Wagels (Australasian Journal of Plastic Surgery)
**Background**: Mandibular reconstruction with autologous bone is a challenging procedure that has benefited from the use of 3D printed cutting guides. However, guides present challenges including long preparatory times, high equipment costs and often imperfect alignment to bone. Recent developments in augmented/mixed reality technology may offer an alternative to address these challenges.